IMPLEMENTASI ALGORITMA NAIVE BAYES TERHADAP DIAGNOSA GEJALA PENYAKIT MATA KATARAK BERBASIS WEBSITE - Danuputri, Chyquitha; Jonathan, Vincent (Universitas Bunda Mulia, 2024)
This research have a purpose to analyse an eye disease. One of the many eye diseases is Cataract. The symptoms that are felt can help determine what type of cataract you are felt so that you can find a fast and effective way of eye treatment. For cataract itself, the Expert System uses the Naive Bayes method to classify the symptoms we experienced so that it helps patients and medical personnel to predict what type of cataract they suffer from. A website-based Expert System requires the role of the Informatics Engineering profession to assist health workers. Where the use of the website itself facilitates access for patients / patients and medical personnel in predicting cataracts suffered by patients / patients based on the symptoms felt. If cataract disease is treated early because the type of cataract suffered has been found based on the symptoms felt, then the right healing method can be done quickly so that cataract disease can be treated as soon as possible. So it will increase the success rate and reduce the risk in the eye treatment process.